Data Processing Training Using Partial Least Squares (PLS) for Management Students on Quantitative Research - Edwar, Rizka Cintya; Khairunnisa, Ayang; Landjang, Xenia Irene Sandy; Mangopo, Yuni Riskita; Damanik, Lisa Gresti Sella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Quantitative research is one of the key pillars in the development of science and technology. In this era of globalization, the ability to conduct quality research has become essential for students, especially management students. One of the popular and effective statistical methods for quantitative research is Partial Least Squares (PLS). This community engagement activity aims to enhance the knowledge and skills of management students in processing quantitative data using PLS methods for their research. The training was conducted over two days with a total of 30 final-semester students participating in the drafting of the thesis. The training material includes basic PLS concepts, measurement models, structural models, the operation of SmartPLS software, as well as the interpretation of the analysis results. The methods used in this training are lectures, demonstrations, and practical practice. The results of this training show an improved understanding of the PLS concept, the ability to operate PLS software, and the ability to correctly interpret analysis results by students. This training is expected to improve the quality of students' research and prepare them for the world of management work